Islamic Education and Moderation: Islamic Religious Education Curriculum as a Tool for Social Transformation - Juliani; Atiqah Zahrah; Isfah Nurhadillah Rizki; Khairunnisa Harahap; Nadilla Yolanda (Yayasan Zia Salsabila, 2024)
The Islamic Religious Education (PAI) curriculum is an important tool to promote social change and foster an inclusive, tolerant, and peaceful society. This article discusses the role of the Islamic Education curriculum in promoting moderation as a key principle in Islamic education. This research uses a descriptive qualitative approach to examine the practice of the Islamic Education (PAI) curriculum in analyzing various ways of expression and making it a tool for social transformation. This moderation approach aims to create harmony in diversity, avoid extremism, and build a clear understanding between religious texts and social reality. Through a holistic curriculum design based on the universal principles of Islam and in line with the historical context, PAI is believed to be an effective tool of social transformation. This study highlights the importance of incorporating moderate values into the curriculum as a strategic approach to developing future generations capable of embracing globalization without losing their Islamic identity.